The Program for the Dissemination of Chinese Culture: Covid-19 Pandemic - Chao Chao, Kuok Wa (2022)
The Confucius Institute in Costa Rica (IC-UCR) has a Program for the Dissemination of Chinese Culture (PDCC). During the Covid-19 pandemic, the PDCC had to adapt to this new reality in order to continue working normally. This research aims, on the one hand, to document the adaptation that the teachers had to continue teaching Chinese language and, on the other hand, to describe the cultural activities carried out during the pandemic. This is an exploratory qualitative study with teachers and participants in cultural activities. The questionnaire and the focus group were used as data collection instruments. As main results, it was obtained that the teachers resorted to the use of information and communication technologies (ICT) to continue the educational process. Also with the ICT, a variety of cultural activities with a very varied theme were carried out.